A simple and rapid HPLC method for the quantitative determination of sodium oleate in flotation study. (September 2019) - Wang, Yunfan; Pan, Zuchao; Qin, Wenqing; Jiao, Fen
Highlights: An HPLC method for detecting the concentration of sodium oleate was proposed. The treatment of flotation samples was described in detail. Advantages of the HPLC method for determining sodium oleate were discussed. This method can be readily adapted for other fatty acids adsorption studies. Abstract: Sodium oleate (NaOL) is an important surfactant chemical used in the separation of oxide minerals by the froth flotation process. The adsorption capacity and the adsorption mechanism of NaOL on the mineral surface are important for understanding flotation behaviour. In this study, a simple, nontoxic and rapid quantitative analysis method of High Performance Liquid Chromatography (HPLC) for residual sodium oleate concentration was proposed and verified. The NaOL was identified in chromatogram by comparison with standard oleic acid. A linear range from 10 to 100 mg/l was observed, and the precision, accuracy, LOD and LOQ were evaluated.